Clustering Method for Fast Deformation with Constraints - Huang, Jin; Liu, Xinguo; Bao, Hujun; Guo, Baining; Shum, Heung-Yeung (2005)
We present a fast deformation method for flexible objects. The deformation of the object is physically modeled using a linear elasticity model with a displacement based finite elements method, yielding a linear system at each time step of simulation. We solve this linear system using a precomputed force-displacement matrix, which describes the object response in terms of displacement accelerations to the forces acting on each vertex. We exploit the spatial coherence to effectively compress the force-displacement matrix to make this method practical and efficient by applying the clustered principal component analysis method. And we developed a method to efficiently handle the additional constraints for interactive user manipulation. At last large deformations are addressed based upon the compressed force-displacement matrix by combining a domain decomposition method and tracking the rotational motions. The experimental results demonstrate fast performances on complex large scale objects under interactive user manipulations.